PENCAHAYAAN ALAMI PADA MASJID AMIR HAMZAH TAMAN IZMAIL MARZUKI JAKARTA - Pratomo, Ardiyansyah Nur Yusuf; Suparman, Agus; Susanto, Remigius Hari; Slameto, Purwanto Joko; HP, Lilik Setiawan; Furuhitho, X. (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The Amir Hamzah Mosque is a mosque located in the Taman Ismail Marzuki complex which was inaugurated by Ali Sadikin on January 7, 1977. The mosque was named Amir Hamzah in memory of an Indonesian writer who was proclaimed a national hero. The renovation of the Amir Hamzah Mosque had been planned for a long time due to the apprehensive condition of the building and the narrow land. To change the shape of an old building into a new one, the quality of natural lighting is needed at the Amir Hamzah Mosque to be able to carry out the functions that take place in the building. The study of natural light at the Amir Hamzah Mosque aims to find out how much the aperture affects the quality of natural light. The choice of location for this study was based on the design of the Amir Hamzah Mosque which has many openings in its facade, so it is interesting to study how large the building allows natural light to enter the space. Natural lighting is influenced by several variables, namely the design of window openings, the orientation of window openings, the area and number of openings, and the glass material. The research method used in this research is descriptive research method, both qualitative and quantitative. From the results of the analysis it was concluded that the design and orientation of window openings at the Amir Hamzah Mosque still experienced a deficit in terms of natural lighting.